2013
DOI: 10.1177/1076029613508600
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin is a Strong Predictor of Multiorgan Dysfunction Syndrome in Patients With Sepsis

Abstract: The level of thrombomodulin not only was able to distinguish the severity of sepsis but also was a significant predictor of MODS development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…In terms of the thrombomodulin/activated protein C system, it has been shown that septic patients that develop MODS have higher levels of thrombomodulin and lower levels of protein C than patients without MODS . Serum thrombomodulin levels are related to mortality and may be used in MODS monitoring in patients with sepsis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the thrombomodulin/activated protein C system, it has been shown that septic patients that develop MODS have higher levels of thrombomodulin and lower levels of protein C than patients without MODS . Serum thrombomodulin levels are related to mortality and may be used in MODS monitoring in patients with sepsis .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the thrombomodulin/activated protein C system, it has been shown that septic patients that develop MODS have higher levels of thrombomodulin and lower levels of protein C than patients without MODS. 22 Serum thrombomodulin levels are related to mortality and may be used in MODS monitoring in patients with sepsis. 23 Decreased protein C levels have long been recognized in patients with sepsis, especially in the presence of DIC or multiple organ failure, and have been associated with outcome.…”
Section: Adamtsmentioning
confidence: 99%
“…Increased serum thrombomodulin levels have been reported in different sepsis syndromes and to be correlated with disease severity. Mihajlovic et al conducted a 1-year prospective study in 60 adults with sepsis and found that the serum thrombomodulin level could be used to predict the severity of sepsis, and also that it was a significant predictor of the development of MODS [ 11 ]. Lin et al conducted a prospective study in 100 adults with sepsis, and also found that serum thrombomodulin level independently predicted the development of disseminated intravascular coagulation (hazard ratio 1.13) and multiple organ dysfunction syndrome (hazard ratio 1.12) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we only determined serum thrombomodulin levels and we did not analyze other biomarkers of coagulopathy or vascular injury such as protein C, protein S [ 11 ], ICAM-1, VCAM-1 and E-selectin [ 10 ]. Therefore, it is difficult to confirm the pathophysiological role of thrombomodulin in sepsis.…”
Section: Limitationsmentioning
confidence: 99%
“…Endothelial dysfunction is central to the pathogenesis of sepsis and is characterized by both macro-and microvascular dysfunction. Markers of endothelial injury are elevated in patients with sepsis and correlate with severity of illness and organ dysfunction [29][30][31]. To determine whether CFH increases endothelial injury in sepsis, we measured ICAM-1, E-selectin, and PAI-1 at 24 hours in mouse plasma ( Fig 3A-3C).…”
Section: Cfh Does Not Affect Circulating Markers Of Endothelial Injurmentioning
confidence: 99%